MUSIK SEBAGAI STIMULASI PERKEMBANGAN BAHASA PADA ANAK USIA DINI : LITERATURE REVIEW - Triningsih, Reni Wahyu; Aryani, Hening Ryan; Mutoharoh, Qismatul (Poltekkes Kemenkes Malang, 2022)
The problem faced by children today is that children have difficulty understanding the content of other people's conversations. This is due to the lack of vocabulary in children. In Indonesia, the prevalence of speech delay in preschoolers is between Five Percent-tenPercent. One of the causes of delays in children's development is the lack of active parents in providing stimulation to their children. This study aims to conduct a review of music as a stimulation of language development in early childhood. This study is a literature review obtained from Three databases Pubmed, DOAJ, and Google Scholar by using inclusion and exclusion criteria. Keywords used in the literature search were